Can the status quo bias help to explain accounting choices? - Stanzani, Lívia Maria Lopes (2021)
The mainstream literature on accounting choices is supported by the rational and opportunistic behavior of managers. However, evidence from Behavioral Finance literature suggests that users often make decisions influenced by behavioral biases, which might affect their choices. Despite the relevance of this subject, to my knowledge, there are no studies that have already explored possible direct interferences of emotional and cognitive biases on managers\' accounting choices. In addition, among the main behavioral biases explored by literature, the status quo bias seems to be directly related to the natural process of choice. So, the objective of this research is to provide empirical evidence about the influence of status quo bias on accounting choices, under a scenario of lack of specific accounting regulation. Then, to achieve this goal, two papers were developed. In the first one, I proposed a qualitative analysis, aiming to verify the influence of the status quo bias on managers\' choices in a low accounting enforcement scenario, which allowed me to understand better and deeply how accounting choices can be influenced by status quo bias. For this purpose, I interviewed managers of public and private companies in relation to the accounting treatment provided by them to the ICMS Accumulated Credit. The evidence suggests that managers\' behavior cannot be explained exclusively through the assumptions of rationality and opportunism, but also by an inertial behavior in relation to the initial accounting treatment (proxy for status quo bias). In the second paper, I applied an empirical investigation and verified the influence of status quo bias on accounting choices related to an asset with changing conditions, under a scenario of low accounting regulation, aiming to verify and validate the qualitative evidence obtained earlier. I analyzed 5,256 Brazilian companies, over nine years, using panel data analysis. The results showed that the previous accounting choice applied in the classification of value-added taxes affects the current accounting choice (evidence of status quo bias), as well as other variables, already presented by the traditional literature (e.g., liquidity, size and leverage). Then, the main contribution of this research is providing evidence about the influence of status quo bias on managers\' decision-making, adding knowledge to accounting choices\' literature. Additionally, the findings of both papers shed light on the need to analyze accounting choices\' determinants by considering Agency Theory and Behavioral Finance assumptions in a complementary way. In practice, it is expected that the research will provide more available information about the determinants of accounting choices to stakeholders, which may benefit them in the decision-making process. Additionally, the study also demonstrates the need to develop a specific accounting standard to provide adequate accounting treatment for value-added taxes.